1996
DOI: 10.1111/j.1476-5381.1996.tb15744.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid modulation of Na +‐K+ pump‐mediated relaxation in maturing airway smooth muscle

Abstract: 1 The ontogeny of the relaxant influence of the airway electrogenic Na+-K+ pump and its potential modulation by corticosteroids were examined in airway smooth muscle (ASM) segments isolated from newborn and adult rabbits. 2 Control and methylprednisolone-treated (MP) ASM segments were half-maximally contracted with methacholine in K+-free buffer and the ASM relaxant responses to Na+-K+ pump activation were subsequently evaluated. Relative to adult ASM, control newborn ASM showed significantly enhanced maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…Furthermore, corticosteroids were administered before and not after ␤ 2 -AR dysfunction (13,19). Finally, corticosteroids can modulate Na ϩ -K ϩ pumpmediated relaxation (24). Again, these mechanisms cannot explain the present data, because relaxation of unchallenged rings was not affected by incubation with BDP.…”
Section: Fig 2 Effect Of 3 ϫ 10contrasting
confidence: 48%
“…Furthermore, corticosteroids were administered before and not after ␤ 2 -AR dysfunction (13,19). Finally, corticosteroids can modulate Na ϩ -K ϩ pumpmediated relaxation (24). Again, these mechanisms cannot explain the present data, because relaxation of unchallenged rings was not affected by incubation with BDP.…”
Section: Fig 2 Effect Of 3 ϫ 10contrasting
confidence: 48%
“…6 Several studies have demonstrated an in vitro antiproliferative effect of corticosteroids on ASM from asthmatic patients. [173][174][175] In addition to their apoptotic effects on airway epithelial cells, 176 corticosteroids have been shown to decrease the proliferation and inflammatory mediator release of lung fibroblasts. 177,178 Some studies have reported that ICS may reduce basement membrane thickness in airway biopsies from asthmatic subjects and may therefore influence subepithelial fibrosis, a major feature of remodeling.…”
Section: Therapeutic Interventions and Remodelingmentioning
confidence: 99%
“…However, in our experiments, dexamethasone treated TSM demonstrated similar isotonic shortening as did control tissues upon acetylcholine exposure and the 4 μM concentration of dexamethasone was chosen because it did not significantly affect isometric force in a separate cohort of TSM strips, suggesting that smooth muscle contractile activation was likely not impaired by dexamethasone. Glucocorticoids also can enhance smooth muscle relaxation by increasing adenylate cyclase activity [36], reducing β 2 receptor desensitization [37], increasing the number of β 2 receptors [38], and increasing Na + /K + pump activity [19]. The latter effect, in particular, may be relevant because it occurs in less than 1 h. Corticosteroids can also reduce smooth muscle proliferation [3941], though one might not expect change in cell number to be relevant within the short time course of our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Grunstein and colleagues [18] have shown that IL-1β and TNF-α increase ASM contractility to acetylcholine (ACh) and impair ASM relaxation with isoproterenol, changes prevented when ASM is pretreated with dexamethasone. However, dexamethasone also increases relaxation with KCl [19] and isoproterenol [20] in contracted TSM even in the absence of a proinflammatory environment suggesting that corticosteroids might exert direct effects on ASM contraction independent of their anti-inflammatory effect. However, since these studies were conducted on rabbit tracheal and bronchial ring segments with intact epithelium, corticosteroids may have exerted their effect indirectly by acting on the epithelium or mucosa rather than on the smooth muscle itself.…”
Section: Introductionmentioning
confidence: 99%